Type IV Sacrococcygeal Teratoma Displacing the Urinary Bladder: Unique Magnetic Resonance Imaging - Sahar Eftekharzadeh; Sorena Keihani; Mehdi Fareghi; Alireza Alamsahebpour; Abdol-Mohammad Kajbafzadeh (Case Reports in Urology)
Type IV sacrococcygeal teratoma is a rare pediatric tumor that is confined to the presacral area with no external component. The signs and symptoms often arise due to mass effect and compression of adjacent organs. Urinary retention is an uncommon presenting symptom in these patients. A wide spectrum of imaging findings may be encountered in cases with sacrococcygeal teratoma because of variability of tumor size and components. We hereby present a unique magnetic resonance urography finding in a type IV sacrococcygeal teratoma which caused bladder displacement. A meticulous and complete resection of tumor with special attention to the pelvic plexus led to preservation of normal voiding function and normal bowel function in this patient.